A Case Report: Regenerative Biodegradable Chin Implant—A Viable Futuristic Option - Medha Bhave; Yogesh Rameshchandra Jaiswal (Indian Journal of Plastic Surgery, 2024)
Chin augmentation can dramatically transform a patient's appearance. Various techniques are in use, each with their specific problems and limitations. We present the first case report from the Indian subcontinent using a custom 3D-printed, bioresorbable polycaprolactone implant. We demonstrate, by appropriate imaging, the replacement of the implant at long-term (22 months) follow-up by patient's own autologous bone formation. An excellent aesthetic result was achieved. Relevant points of technique, as well as pertinent properties of the material, are discussed. This material has been used in neurosurgery and in the management of orbital fractures. Yet, worldwide, very few (3–4) cases of chin implant have been done using this material. We believe this to be a useful and sustainable material, offering several advantages, as set out in the case report.